Desenvolvimento profissional e pessoal dos técnicos administrativos em educação do CCSH/UFSM, frente aos desafios da expansão universitária - Silva, Jane Santos da (2014)
This research was developed with the purpose of identifying the need for professional and personal development of Administrative Technical Education ( TAE ) of a Federal Institution of Higher Education in Social and Human, and propose a Plan for Professional and Personal Development for same , keeping in view the demands of the changing and expanding, experienced by Federal Institutions of Higher Education ( IFES ) process. For this, we carried out a survey of descriptive character, drawing on quantitative methodologies. The research sample consisted of 51 technical and administrative staff of a Center for Teaching a Federal Institution of Higher Education, to which a questionnaire in which we sought to assess the needs for training, through a set of questions was applied grouped into key constructs by area. In terms of personal development, be - sought thematic commonly associated with human behavior at work, such as motivation, creativity, leadership, dealing with conflict, stress, innovation and ethics and sustainability. Data were analyzed by means of software " Windows Excel", "SPSS 18" and "SAS 9". Simple descriptive statistics, correlations were performed. The results showed that the TAE have needs for professional development involving new information technology, administrative and managerial processes among others. Concerning behavioral issues that motivate evidenced by achievement, and creativity in general and median or inexpressive. The responses guided the preparation of a Plan for Professional & Personal Development Professional Development in which it was proposed in two stages, the first courses with greater than or equal to 70% acceptance rates in the second stage, those who obtained less indication 70%. In terms of Personal Development it was found that majorities of TAE working alone in their respective departments and not have moments of relaxation, talk to exchange experiences, to have a coexistence and integration, there is an invisible insulation, promoted by the activities and obligations meet, which contradicts the need for affiliation presented with high approval rate of 61.57 % of TAES. The implementation of the Plan for Professional and Personal Development of TAE / CCSH promote the growth of the quality of life of the professionals involved and the Center gain more empowered and happy servers, reflecting the efficiency and effectiveness of services provided.